Vocal Symptoms and Associated Risk Factors between Male and Female University Teachers - Korn, Gustavo Polacow; Park, Sung Woo; Pontes, Antonio Augusto de Lima; Pontes, Paulo (International Archives of Otorhinolaryngology, 2018)
Introduction Many recent studies on teachers warn of the adverse effects that voice problems have on work performance. However, only a few of these studies included university teachers.Objective To compare the vocal symptoms and risk factors between male and female university teachers in a private institution within the city of São Paulo.Methods In a cross-sectional survey, a voice self-evaluation form prepared by the Ministry of Labor in Brazil was administered to 846 university teachers at a private institution in the city of São Paulo.Results The percentage of hoarseness, vocal tract discomfort, neck pain and foreign body sensation was significantly higher in female than in male subjects. A significantly higher percentage of males participated in other professional activities in addition to teaching, reported working in a calm environment compared with working in a moderately or severely tense and stressful environment, and rated themselves as calm, slightly stressed and anxious or moderately stressed and anxious rather than very stressed and anxious. A significantly higher percentage of females spent most of their time teaching compared with performing other professional activities, and rated themselves as chatty or impulsive.Conclusion Among university teachers, a significantly higher percentage of females than males reported hoarseness, vocal tract discomfort, neck pain and foreign body sensation. Some risk factors related to work organization, workplace environment, voice care and quality of life variables were related to this higher prevalence in females.
Keywords: dysphonia; risk factors; faculty